The endophytic fungi from South Sumatra (Indonesia) and their pathogenecity against the new invasive fall armyworm, Spodoptera frugiperda - Mimma Gustianingtyas; Siti Herlinda; Suwandi Suwandi (Society for Indonesian Biodiversity, 2021)
Abstract. Gustianingtyas M, Herlinda S, Suwandi. 2021. The endophytic fungi from South Sumatra (Indonesia) and their pathogenicity against the new invasive fall armyworm, Spodoptera frugiperda. Biodiversitas 22: 1051-1062. Maize in Indonesia is currently experiencing attacks and outbreaks of the new invasive fall armyworm, Spodoptera frugiperda. The S. frugiperda larvae emerge from the leaf midrib when eating, after hiding in the maize stalk so that it is difficult to control by contact. This study aimed to find out the endophytic fungi from the roots of maize, banana and chili in South Sumatra and to determine their pathogenicity against S. frugiperda larvae. The endophytic fungi were isolated from the plant roots. Fungal isolates proven to be endophytic were dropped (1 × 106 conidia mL?1) on the second instar larvae. The result showed that the endophytic fungi found were 8 isolates consisting of the genus, Aspergillus sp., Beauveria sp., Chaetomium sp., and Curvularia sp. First report of Aspergillus sp., Chaetomium sp., and Curvularia sp. have insecticidal activity against S. frugiperda larvae. However, the two most pathogenic isolates were JgCrJr and JgSPK isolates of Beauveria sp. with larval mortality of 29.33% and 26.67%, respectively, and could reduce the emergence of S. frugiperda adults up to 44%. So, the two isolates of Beauveria sp. have a high potential to be developed to control S. frugiperda larvae in maize both in the lowlands and the highlands.